ALAT DESTILASI SEDERHANA SEBAGAI MEDIA EDUKASI UNTUK MENINGKATKAN MINAT WIRAUSAHA SISWA-SISWI SMA IT AL KAMAL NW NARMADA - Dina Asnawati; Saprini Hamdiani; I Made Sudarma; Nurul Ismilayli (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram, 2015)
Abstrak: Peningkatan Sumber Daya Manusia dalam pelaksanaannya menghadapi banyak kendala terutamaÃÂ dalamÃÂ halÃÂ saranaÃÂ danÃÂ prasaranaÃÂ terutamaÃÂ bagiÃÂ sekolah-sekolahÃÂ swastaÃÂ diÃÂ pedesaan LombokÃÂ Barat.ÃÂ SalahÃÂ satunyaÃÂ adalahÃÂ SMAÃÂ ITÃÂ AlÃÂ KamalÃÂ NWÃÂ NarmadaÃÂ yangÃÂ terletakÃÂ diÃÂ Desa Golong Kecamatan Narmada, Lombok Barat. Sekolah yang berdiri tahunÃÂ 2008 ini belum memiliki fasilitasÃÂ ruangÃÂ danÃÂ alatÃÂ laboratorium.ÃÂ HalÃÂ iniÃÂ sangatÃÂ menyulitkanÃÂ siswaÃÂ untukÃÂ dapatÃÂ memahami konsep-konsepÃÂ IPAÃÂ secaraÃÂ lebihÃÂ mendalamÃÂ tanpaÃÂ disertaiÃÂ praktikum.ÃÂ SehinggaÃÂ perluÃÂ dilakukan inovasiÃÂ denganÃÂ memanfaatkanÃÂ barang-barangÃÂ bekasÃÂ yangÃÂ mudahÃÂ diperolehÃÂ untukÃÂ dijadikanÃÂ alat peragaÃÂ sederhana.ÃÂ SalahÃÂ satuÃÂ inovasiÃÂ yangÃÂ telahÃÂ dilakukanÃÂ adalahÃÂ perancanganÃÂ danÃÂ pembuatan sendiriÃÂ alatÃÂ praktikumÃÂ destilasiÃÂ sederhana,ÃÂ untukÃÂ membantuÃÂ siswaÃÂ memahamiÃÂ konsepÃÂ destilasi serta penerapannya dalam industri. Diharapkan pengabdian ini akan meningkatkan kreatifitas dan minatÃÂ paraÃÂ siswa/siswiÃÂ SMAÃÂ ITÃÂ AlÃÂ KamalÃÂ untukÃÂ mengembangkanÃÂ penggunaanÃÂ alatÃÂ destilasi sederhana tersebut dalam bidang praktis seperti pertanian sehingga dapat juga menigkatkan jiwa kewirausahaan siswa.Kata kunci : alat destilasi sederhana, praktikum, wirausahaAbstract: ImprovementÃÂ ofÃÂ humanÃÂ resourcesÃÂ facesÃÂ manyÃÂ challenges,ÃÂ especiallyÃÂ inÃÂ termsÃÂ of facilities and infrastructure, especially for private schools in rural, West Lombok. One of the high schools that face the same problem is the High School IT Al Kamal NW Narmada located in the villageÃÂ ofGolongÃÂ DistrictÃÂ ofÃÂ Narmada,ÃÂ LombokÃÂ Barat.ÃÂ SchoolÃÂ wasÃÂ establishedÃÂ inÃÂ 2008ÃÂ butÃÂ have no adequateÃÂ classroomÃÂ facilitiesÃÂ andÃÂ laboratoryÃÂ equipment.ÃÂ ItÃÂ isÃÂ veryÃÂ difficultÃÂ forÃÂ studentsÃÂ to understandÃÂ scienceÃÂ conceptsÃÂ inÃÂ moreÃÂ depthÃÂ withoutÃÂ laboratoryÃÂ workÃÂ activity. ThereforeÃÂ itÃÂ needs innovationÃÂ forÃÂ simpleÃÂ laboratoryÃÂ workÃÂ activityÃÂ byÃÂ utilizingÃÂ second-handÃÂ goodsÃÂ thatÃÂ readilyavailable.ÃÂ TheÃÂ simpleÃÂ innovationÃÂ thatÃÂ hasÃÂ beenÃÂ introducedÃÂ isÃÂ toÃÂ designÃÂ andÃÂ manufactureÃÂ simple distillationÃÂ apparatusÃÂ inÃÂ orderÃÂ toÃÂ helpÃÂ studentsÃÂ understandÃÂ theÃÂ conceptÃÂ ofÃÂ distillationÃÂ andÃÂ its applicationÃÂ inÃÂ theÃÂ industry.ÃÂ ThisÃÂ approachÃÂ isÃÂ expectedÃÂ toÃÂ increaseÃÂ creativityÃÂ andÃÂ interestÃÂ ofÃÂ the student especially from SMA IT Al Kamal to develop simple destilation apparatus for practical purposes (e.g in agriculture) so that it is espected that student has entrepreneurs skills.ÃÂ Keywords :simple distillation device,ÃÂ laboratory work, entrepreneur